Requerimientos y posibilidades para la administración de riesgos de precios del arroz en Colombia (2011)
This article documents both the size and trends of rice price fluctuations in Colombia throughout the chain value. It also discusses possibilities for economic agents to implement both conventional and market based price risk management strategies and mechanisms. Specifically, it contends the importance for rice farmers to hold control on the spot market of paddy rice by extending own drying and storage facilities. Main requisites and present constraints to organize the rice cash market as well as the future and derivative market for rice in the Colombian Board of Trade BMC are presented. The whole discussion aims at reducing the impact of rice price volatility upon the financial performance of the rice business across the supply chain.